Golden Bear Will Lift First Food, Clothes from Here - Cleek, John L. (Unknown)
The Golden Bear, training ship of the California Maritime Academy, scheduled to sail from Morrow Cove Jan. 15, on a mission of friendship to France, Italy, and Greece with a cargo of food and clothing contributed by the generous residents of California, will not sail empty on the first leg of this memorable voyage, but will receive her first consignment through the cooperation of Vallejo and Solano County residents. Plans for collecting, a large quantity of food and clothing were started Thursday noon when Vallejo Rotary Club President D.B. Park named Ernest Wichels chairman of a city wide committee.